Impact of ball material change from celluloid to plastic on game statistics in elite women table-tennis - Goh, W. X.; Lee, M. J. C. (International Journal of Performance Analysis in Sport, 2022)
This study compared the statistics of 24 matches played by elite women table-tennis players using the old celluloid versus new plastic balls to provide insight into the on-court adaptations made. Matches played by five, top-10 world ranked female players, using the celluloid (n = 12) versus plastic balls (n = 12) in international competitions from 2011 to 2017 were analysed. The results showed that the average strokes per point and point duration were approximately 15% and 13% shorter when playing with the plastic (4.79 ± 0.59; 3.91 ± 0.54s) compared with celluloid balls (5.52 ± 0.62; 4.49 ± 0.53s). Rally intensity was, however, higher for matches played with plastic (1.57 ± 0.27 strokes/s) versus celluloid (1.49 ± 0.25 strokes/s) balls. Overall work-rest ratio was smaller by 3% for the former versus the latter. The trade-off between more intense rallies and more rest time on energy expenditure remains unknown and would be an interesting area to investigate for targeted prescriptions of training programmes.